2001
DOI: 10.1186/bf03500883
|View full text |Cite
|
Sign up to set email alerts
|

Olive domestication from structure of oleasters and cultivars using nuclear RAPDs and mitochondrial RFLPs

Abstract: RAPD profiles of 121 olive cultivars were compared to those of 20 natural oleaster populations from eastern and western parts of the Mediterranean Basin. Considering the proximi ties of RAPD profiles between cultivars and eastern or western oleaster populations, clear differences appeared between groups of cultivars. Cultivars from Israel, Turkey, Syria, Greece and Sicily were, with very few exceptions, close to the eastern group of oleasters; in contrast, clones from Continental Italy, Continental France, Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 24 publications
5
66
0
9
Order By: Relevance
“…By contrast, both core collections proposed in the current study accurately reflected the geographic distribution of cultivated olive, and demonstrated the high admixture level, since 48% and 52% of 50 and 94 entries, respectively, originated from the central Mediterranean zone. Our proposal is supported by the fact that the central Mediterranean zone is a hybrid area between the eastern and western zones, as shown by the admixed inferred ancestry of most of the genotypes sampled in this area [52], [96]. Strikingly, when comparing the varietal composition in the CC 94 core collection with those previously published for olive, we found that only 11 and 12 varieties were shared with those reported by Diez et al [66] and Belaj et al [51], respectively.…”
Section: Discussionsupporting
confidence: 85%
“…By contrast, both core collections proposed in the current study accurately reflected the geographic distribution of cultivated olive, and demonstrated the high admixture level, since 48% and 52% of 50 and 94 entries, respectively, originated from the central Mediterranean zone. Our proposal is supported by the fact that the central Mediterranean zone is a hybrid area between the eastern and western zones, as shown by the admixed inferred ancestry of most of the genotypes sampled in this area [52], [96]. Strikingly, when comparing the varietal composition in the CC 94 core collection with those previously published for olive, we found that only 11 and 12 varieties were shared with those reported by Diez et al [66] and Belaj et al [51], respectively.…”
Section: Discussionsupporting
confidence: 85%
“…As previously shown in Mediterranean wild and domesticated olives (Besnard et al 2002, 2007; Breton et al 2006), all eastern Mediterranean accessions carried E1, whereas lineages E2 and E3 were only observed in the western Mediterranean Basin, but with a relatively low frequency in cultivars (16%; Besnard et al 2001a). These cpDNA lineages again confirm that cultivated olive has been selected from different gene pools from both eastern and western regions of the Mediterranean Basin (Besnard et al 2001c). …”
Section: Discussionsupporting
confidence: 71%
“…Domestication has been documented and previously reported by several authors (e.g. Zohary, 1994), with the assertion that cultivars moved westward with human migration supported by several authors (Besnard et al. , 2001a; Belaj et al.…”
Section: Introductionmentioning
confidence: 55%
“…, 1999) and random amplified polymorphic DNA (RAPD) (Fabbri et al. , 1995; Besnard et al. , 2001a) and recently with simple sequence repeat (SSR) analysis for cultivar identification (Cipriani et al.…”
Section: Introductionmentioning
confidence: 99%